Niger : Second Review Under the Extended Credit Facility Arrangement, and Request for Modification of a Performance Criterion-Press Release; Staff Report; and Statement by the Executive Director for Niger. (IMF Staff Country Reports; Country Report, 2018)
This paper discusses Niger's Second Review Under the Extended Credit Facility (ECF) Arrangement, and Request for Modification of a Performance Criterion (PCs). With all PCs met, implementation has been satisfactory, except for the large miss of the indicative target on fiscal revenue augmentation-an important concern, considering that it is instrumental for fiscal consolidation and fiscal space to address pressing social and infrastructure needs. The indicative target on domestic arrears clearance in the first quarter of 2018 was also missed, but by less than the overperformance in 2017. The structural reform agenda is advancing, though more slowly than envisaged. The IMF staff supports the conclusion of the second review under the ECF.